Ritus Tombor Maghi: Mempererat Hubungan Harmonis Islam-Kristen di Kabupaten Fakfak - Marthinus Ngabalin; Lindra Y. Camerling; Zacharias Sahureka; Bhayanangky A. Lewier (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
This article examines the Tombor Maghi ritual as a cultural practice and form of lived religion in fostering interreligious relations in Fakfak Regency, West Papua. Initially, Tombor Maghi was a customary ritual associated with the collection of bridewealth in marriage traditions. Over time, however, the ritual has transformed into a medium of social solidarity manifested in the construction of churches and mosques, educational support, and various community social activities. This study aims to describe the development of Muslim–Christian relations in Fakfak, analyze Tombor Maghi as a practice of lived religion, and explain its contribution to strengthening interreligious relations. The research employs a qualitative method with an ethnographic approach through interviews, observation, and documentation. The findings reveal that Tombor Maghi functions as a medium of interreligious dialogue, social solidarity, and community cohesion. Furthermore, the ritual represents a locally grounded practice of lived religion that reinforces harmony and social peace within a multicultural society.